Long-leg spica casts demonstrate superior outcomes in developmental dysplasia of the hip: a multi-center retrospective analysis of failure risks and protective factors - Zheng, Zibing; Yu, Weiguang; Chen, Zhao; Lin, Jinrun; Lin, Jinluan; Chen, Hui (Frontiers in Pediatrics, 2025)
ObjectivesWhile both short- and long-leg spica casts present viable options after closed reduction (CR) in developmental dysplasia of the hip (DDH), comprehensive comparative studies are needed to guide clinical practices. This multi-center retrospective study aimed to evaluate their effectiveness in treating DDH and identify predictors of treatment failure.MethodsThis retrospective study analyzed 146 DDH patients (0–18 months) treated with closed reduction and spica casts (70 short-leg vs. 76 long-leg) at two tertiary centers (2005–2024). Incident-free survival (time from casting to failure: re-dislocation, imaging-confirmed reduction loss, or surgical conversion) was analyzed via Kaplan–Meier/Log-rank tests. A multivariable Cox model evaluated eight variables: cast type, age (>6 vs. ≤6 months), sex, laterality (bilateral/unilateral), IHDI grade (IV/III), birth presentation, delivery mode, and family history, allowing quantification of independent predictors associated with treatment failure risks.ResultsThe analysis of 146 DDH cases (70 short-leg vs. 76 long-leg casts) revealed significant outcome differences between cast types. Patients receiving long-leg spica casts demonstrated substantially higher 6-month incident-free survival rates (84% vs. 68%, Log-rank p < 0.05), with multivariable Cox regression confirming long-leg casting as an independent protective factor (HR = 0.45, 95% CI 0.32–0.64, p < 0.001). The analysis identified three significant risk predictors: older age (>6 months) increased failure risk by 89% (HR = 1.89, 95% CI 1.02–3.51), bilateral involvement elevated risk by 78% (HR = 1.78, 95% CI 1.25–2.54), and IHDI IV dysplasia doubled failure likelihood (HR = 2.15, 95% CI 1.45–3.18). Notably, cephalic presentation showed a protective trend (HR = 0.67, 95% CI 0.48–0.93), while delivery mode and family history did not reach statistical significance.ConclusionsLong-leg spica casting shows superior biomechanical stability in DDH management post-CR, particularly for high-risk patients. These findings support its preferential use in patients with bilateral involvement, advanced dysplasia, or older age (>6 months).